2013
DOI: 10.1371/journal.pone.0084465
|View full text |Cite
|
Sign up to set email alerts
|

An Inducible, Ligand-Independent Receptor Activator of NF-κB Gene to Control Osteoclast Differentiation from Monocytic Precursors

Abstract: Osteoclasts are bone-resorbing cells that are critical for the normal formation and maintenance of teeth and skeleton. Osteoclast deficiency can contribute to heterotopic ossification (HO), a pathology that is particularly detrimental to the mechanical functions of joints, valves and blood vessels. On the other hand, osteoclast over-activity is a major cause of osteoporosis. A reliable method for controlled generation of osteoclasts would be useful as a potential autologous cell therapy for HO, as well as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…We previously validated the same iRANK construct using a murine preosteoclastic cell line, RAW264.7. When treated with 50 n m of CID, iRANK‐expressing RAW264.7 cells showed induction of tartrate‐resistant acid phosphatase (TRAP) activity as well as formation of mineral resorbing multinucleated osteoclasts . The current studies confirmed the expression and function of CD68‐driven iRANK in macrophage precursors of transgenic mice, but no expression or function of this construct was observed in bone marrow‐derived (BMD) or spleen‐derived osteoclast precursors.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…We previously validated the same iRANK construct using a murine preosteoclastic cell line, RAW264.7. When treated with 50 n m of CID, iRANK‐expressing RAW264.7 cells showed induction of tartrate‐resistant acid phosphatase (TRAP) activity as well as formation of mineral resorbing multinucleated osteoclasts . The current studies confirmed the expression and function of CD68‐driven iRANK in macrophage precursors of transgenic mice, but no expression or function of this construct was observed in bone marrow‐derived (BMD) or spleen‐derived osteoclast precursors.…”
supporting
confidence: 61%
“…The iRANK dimerization domain allows interaction with a chemical inducer of dimerization (CID) drug. As RANK requires trimerization for effective signaling, we have engineered two FK506‐derived dimerization domains fused to the RANK cytoplasmic domain to ensure successful oligomerization . Thus, in this system, the fusion protein (iRANK) is functionally inert unless directed to oligomerize by the addition of the CID, AP20187.…”
mentioning
confidence: 99%
“…Further, our lab has previously demonstrated that this system can be used to engineer inducible bone resorbing osteoclasts from the monocyte-macrophage RAW264.7 cell line, in which it is important to note that monocytes are a common precursor to both macrophages and osteoclasts. [27]…”
Section: Discussionmentioning
confidence: 99%
“…Tissue targeting may be essential to avoid damage to skeletal bone; for example, if osteoclasts or nanoparticles carrying osteoclastic differentiation factors could be targeted to valve tissue, they may reverse CAVD. [6] However, even if successful, mineral resorption may leave behind damaged leaflets. Molecular imaging of these events may provide biomarkers for clinical and research monitoring far in advance of critical stenosis.…”
Section: How Do We Develop Improved Treatments For Cavd?mentioning
confidence: 99%
“…[49] Furthermore, new techniques to engineer monocytes that conditionally differentiate into OPG-resistant osteoclasts have been recently developed. [6] Thus, approaches to control osteoclast differentiation and/or locally deliver autologous osteoclasts represent potential novel therapeutic modalities to treat or even regress CAVD.…”
Section: Dysregulated Mineral Metabolism and Osteoclast Deficiency Inmentioning
confidence: 99%